Linguistic Features of Translation - I., Mazhidova Kh. (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The philosophy of the word, or the philosophy of philology, assumed the understanding of the human word as a divine gift, an instrument for organizing and creating the world, society, the universe - and this attitude to the word is fully preserved in spiritual literature and ethics of speech. A separate topic is the evolution of the Russian philosophy of the word, which has its origins in the works of M.V. Lomonosov, who wrote: "Whoever goes deeper into it from time to time, using the leader of the general philosophical concept of the human word, he will see an immensely wide field, or, better to say, barely has a sea."